Mechanistic insights into pachymic acid’s action on triple-negative breast Cancer through TOP2A targeting - Ming Liu; Li Zheng; Yang Zhang; Jinhui Tian (Scientific Reports)
Abstract Triple-negative breast cancer (TNBC) is characterized by the absence of estrogen and progesterone receptors, and lack of human epidermal growth factor receptor 2 (HER2) expression. Traditional Chinese medicine (TCM) has demonstrated promising efficacy in treating TNBC. This study explored the mechanisms of pachymic acid (PA) on TNBC by merging network pharmacology with experimental validation. We acquired Microarray data of TNBC from the Gene Expression Omnibus (GEO). The related targets of PA were predicted and screened using the following 6 databases: Swiss Target Prediction, HERB (Herbal Medicine Database), ETCM (Encyclopedia of Traditional Chinese Medicine), BATMAN (Bioinformatics Analysis Tool for Molecular Mechanism of Traditional Chinese Medicine), HIT (Herb Ingredients’ Targets Database), and PharmMapper. The STRING interaction network analysis tool was used to create Protein-Protein Interaction (PPI) networks. Enrichment analysis included Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). We conducted a pan-cancer analysis, tumor immune microenvironment analysis, and molecular docking. We performed cell experimental, included cytotoxicity assay, apoptosis analysis, proliferation assay, and migration and invasion assays. PA has potential for treating TNBC with the target of TOP2A, and platinum drug resistance possibly serving as the KEGG pathway through which PA exerts its therapeutic effects. PA is involved in processes such as nuclear division, chromosome segregation, mitotic nuclear division, condensed chromosome formation, and protein C-terminus binding. PA probably exert its therapeutic effects through the tumor immune microenvironment, involving elements such as Dendritic cells activated, Eosinophils, Macrophages M0, Macrophages M1, and T cells CD4 memory activated. The therapeutic effects of PA may vary across different subtypes of TNBC such as TNBC-BL1, TNBC-Metaplastic, and TNBC-BL2. This study provides compelling evidence that PA holds significant promise as a therapeutic agent for TNBC, primarily through its action on TOP2A and its influence on the TNBC.